Analisis Faktor Risiko Kejadian Malaria Di Wilayah Kerja Puskesmas Bosnik Kecamatan Biak Timur Kabupaten Biak Numfor Papua Tahun 2006. - Yawan, Semuel Franklyn; Sulistiyani, Sulistiyani; Barodji, Barodji (Jurnal Kesehatan Lingkungan Indonesia, 2006)
ABSTRACT Background: Biak Regency is one of regencies in Papua with high rate in malaria incidences, average clinical malaria rate is 48,677 cases in a year, with its Annual Malaria Incidence (AMI) average of 395,880/00 per year. The working Area of Bosnik Community Health Centre constitutes endemic region as the highest HIA (High Incidence Area), its average AMI’s rate of 395,88 0/00, which is far above national rate (31,090/00). This research has purpose to analyze malaria incidences on Working Area Bosnik Community Health Centre, Biak Numfor regency of Papua Province. Methods: Type of this research was on observational with case control approach. Case group were people whom positively suffer tropical malaria, which signed by results of blood examination positive with contain Plasmodium falciparum, while control group are they who were not suffer malaria disease signed by such results on his blood examination negative with contain Plasmodium falciparum. Control selected according to several criteria such sex, age, or no more three years in difference. Result: Results showed, the risk factor upon malaria incidences were the lower education with OR value = 4,28(95%CI=0,981 - 18,721), impermanent floor construction, OR value = 5,182 (95%CI = 1,183 - 22,238), ceiling house existed (protective factor) ) OR value = 0,696 (95%CI = 0,531-0,912), water puddle around their residences OR value = 3,683(95%CI=1,062-12,711), custom to take no mosquito-net OR value = 5,182 (95%CI=1,339-20,058), custom to take hang clothes insides home OR value = 16,923 (95%CI=1,938-147,767), disobedience to take administer his or her medicines OR value = 5,182 (95%CI=1,339-20,058), go outside in night time custom OR value = 4,680(95%CI=1,290-16,983). Conclusion: It requires such monitoring and evaluating about spraying and mosquito-net distribution. Monitoring requires take places to inform the necessity for using the mosquito-net, obediences to take medicine, their residences environment sanitation particularly about water puddle, and avoiding stay outside at night. Keywords : risk factor, malaria incidence, Plasmodium falciparum